Towards a Digital Control Tower: The Use of Augmented Reality Tools to Innovate Interaction Modes - Bagassi, S.; Corsi, M.; Santarelli, R.; Teutsch, J.; Garcia Lasheras, R.; Amaro Carmona, M.A.; Groskreutz, A.R. (SESAR Joint Undertaking, 2022)
This paper describes the EU-funded project “Digital Technologies for Tower” (PJ05-W2 DTT) Solution 97.1 validation exercises by focusing on the simulation platforms and exploited technologies to demonstrate how Virtual/Augmented Reality along with Tracking Labels, Air Gestures and Attention Guidance can allow the air traffic controller to increase head-up time, even in low visibility conditions, to lower the time to react to critical or alerting situations, to reduce the workload, and to improve Situational Awareness and productivity. Important guidelines to further enhance the proposed solutions achieving higher levels of maturity can be drawn starting from the results obtained during the Sol 97.1 validation campaign.